Caring of Premature Infants with Kangaroo Method - Iranmanesh (Iran University of Medical Sciences, 1988)
Is it possible to discharge a 2-3 hours, 1134 g weight breast feeding newborn in 24 -36 hours from hospital?   Yes, in Materno Pediatric Hospital located in Bogatto-Clombia it is a routine. It is an approach to prevent high costs and nosocomial infections. It also used to establish a deep relationship based on natural and instinct process.   Newborns who are in satisfactory clinical situations, guide to their mothers only after 2-3 hours of birth without any concerns about their immaturity. Mother also are taught about feeding and warming their newborns through skin to skin contact by placing the kids between their breasts in upright position.